Unlocking the full potential of nearshoring: A conceptual delivery model for proximity offshoring services - Guedes, J.; Pereira, L. (International Journal of Productivity and Quality Management, 2024)
Nearshoring practices have been used in the delivery of information system services for the past decades, being seen by many companies as a core component of their offering or even as a key differentiator of their ways of working. Although widely used, these practices are not fully understood by the academic community nor by practitioners - unlike offshoring in which risks, benefits, challenges, and success factors are widely understood. In several cases framed by delivery models and frameworks that can maximise delivery, nearshoring is still in its infancy in this regard. This research aims to advance on this space, having as main objective to develop a conceptual model that can maximise the delivery output using nearshoring services without compromising on delivery quality or increasing delivery risks from a vendor perspective. To do so, the authors engaged with ten experts using a Delphi method followed by a focus group.